TEACHING AND LEARNING APPROACHES FOR INFANTS AND TODDLERS AT TASKA AL-BAGHDADI : A CASE STUDY - NURUL SYAFIQAH JAFINAN@JAFRIAN; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study was conducted to examine the teaching and learning approaches implemented at Taska Al-Baghdadi through an interview with an experienced educator. The findings reveal that the learning through play approach forms the core foundation in supporting children’s holistic development, covering cognitive, physical, emotional, and social aspects. Key strengths include the use of creative teaching aids, well planned thematic activities according to age groups, and an emphasis on enjoyable learning experiences beyond academics. However, several challenges were identified, such as classroom management issues and helping new children adapt to daily routines. In conclusion, the teaching practices at Taska Al-Baghdadi reflect a strong commitment to providing high quality early childhood education aligned with child development theories and parents’ aspirations for their children’s well being and overall growth from an early age.